Effects of Low-Dose Ketamine Combined With Propofol on Phosphorylation of AMPA Receptor GluR1 Subunit and GABAA Receptor in Hippocampus of Stressed Rats Receiving Electroconvulsive Shock. Issue 1 (March 2015) - Chen, Jing; Peng, Li-hua; Luo, Jie; Liu, Li; Lv, Feng; Li, Ping; Ao, Li; Hao, Xue-chao; Min, Su
Abstract : Objectives: To investigate the effects of low-dose ketamine combined with propofol on the antidepressant efficacy in stressed rats undergoing electroconvulsive shock (ECS) and its impact on phosphorylation of alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptor subunit glutamate receptor 1 (GluR1 ) and γ-aminobutyric acid receptor subunit A (GABAA R). Methods: Sprague-Dawley rats were stressed by chronic unpredictable mild stress. Fifty stressed rats were randomly divided into 5 groups (n = 10 per group): depression group (with no application, group D), ECS group (applied with ECS after intraperitoneal injection of isotonic sodium chloride solution, 8 mL/kg, group E), ketamine + ECS group (applied with ECS after intraperitoneal injection of ketamine, 10 mg/kg, group KE), propofol + ECS group (applied with ECS after intraperitoneal injection of propofol, 80 mg/kg, group PE), and ketamine + propofol + ECS group (applied with ECS after intraperitoneal injection of ketamine, 10 mg/kg, and propofol, 80 mg/kg, group KPE). All groups except group D underwent ECS once a day for 7 consecutive days. Sucrose preference test, open-field test, and Morris water maze were performed to assess the depressive behavior. Phosphorylation of GluR1 and GABAA R were evaluated by Western blot. Results: Compared with group D, sucrose preference percentage and open-field scores were increased after ECS application in the 4 other groups; rats in group E reported prolonged escape latency and shortened space exploration time, whereas the escape latency were decreased and space exploration time were prolonged in group KPE; the ratio of p -GluR1 /p-GABAA R in hippocampus were increased in the 4 other groups. When using group E as control, rats in group KPE exhibited higher sucrose preference percentage and open-field scores; the escape latency was shortened and space exploration time was prolonged in groups KE, PE, and KPE; the ratio of p -GluR1 /p-GABAA R in the hippocampus was up-regulated in groups KE and KPE. When compared with groups KE and PE, the rats in group KPE exhibited higher sucrose preference percentage and open-field scores, the escape latency of group KPE was shortened and space exploration time was prolonged, the ratio of p -GluR1 /p-GABAA R in the hippocampus of group KEP is between those of groups KE and PE. Conclusions: Low-dose ketamine combined with propofol may play a role in enhancing the antidepressant efficacy of ECS in stressed rats, ameliorating the cognitive impairment associated with ECS by balancing the expression of p -GluR1 and p-GABAA R in the hippocampus of stressed rats.